Nanostructure development in multicomponent polymer systems characterized by synchrotron X-ray scattering. (August 2016) - Dencheva, Nadya; Stribeck, Almut; Denchev, Zlatan
Graphical abstract: Highlights: Three synchrotron X-ray studies in two multicomponent polymer systems are presented. Transcrystallinity in microfibrillar composites is quantified by WAXS, SEM and TEM. Strain-induced crystallization is found by SAXS in HDPE/PA6 microfibrilar systems. Gradients in loaded PA6 microcapsules are shown by scanning with X-ray microbeams. Abstract: Modern synchrotron beamlines equipped with two-dimensional detectors and high-flux microfocus devices offer interesting possibilities for polymer characterization. This work presents three synchrotron X-ray studies performed in specific multicomponent polymer systems. In the first study, quantification of transcrystallinity in microfibrillar composites (MFC) by wide-angle X-ray scattering (WAXS) and a direct relation between the mechanical properties of the composites and the thickness of the transcrystalline layers is presented. The second study demonstrates monitoring of nanostructure development under controlled strain in MFC and their precursors by small-angle X-ray scattering (SAXS). A specially developed procedure for data treatment that uses the Chord Distribution Function formalism permitted to prove reversible strain-induced crystallization of matrix material in the MFC materials. In the third study, a 5 × 5 μm high flux X-ray beam was used to scan in WAXS mode polymer microcapsules (average diameters of 20–50 μm) with polyamide shells in which various solid payloads were incorporated by in-situ polymerization. Exfoliation/intercalation phenomena and local inhomogeneity at micron scale are studied in clay and metal containing polyamide microcapsules that constitute a new platform for the development of polymer hybrids or smart micro devices. It was concluded that relating microscopy and/or mechanical data of various polymer samples to their synchrotron WAXS/SAXS patterns helps to understand the structure–properties relationship in complex polymer systems with controlled composition, morphology and nanostructure.